2021
DOI: 10.1080/21655979.2021.1945894
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the correlations between interleukin-27 (IL-27) and immune-inflammatory imbalance in preterm birth

Abstract: Preterm birth (PTB) is an immune-inflammatory disease that needs to be resolved. This study aimed to identify the role of interleukin-27 (IL-27), an immunomodulatory factor, in PTB and its associated mechanisms. Here, we analyzed the high-throughput of samples data from the maternal-fetal interface to the peripheral circulation obtained from public databases and reported that the elevated IL-27 was involved with the onset of PTB. Further bioinformatics analyses (e.g. GeneMANIA and GSEA) revealed that IL-27 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 105 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…This hypothesis is also reinforced by the increased levels of Ifn-γ , typically linked with a pro-inflammatory state during pregnancy complications [ 41 ]. Il27 , correlated with an immune–inflammatory imbalance in the pre-term [ 42 ], showed increased expression in Hmox1 −/− uteruses. Similarly, the upregulation of Il11 , was previously associated with inflammation and pre-eclampsia features in mice [ 43 ] and Il1b , linked to idiopathic recurrent implantation failure [ 44 ], indicated a pro-inflammatory milieu.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also reinforced by the increased levels of Ifn-γ , typically linked with a pro-inflammatory state during pregnancy complications [ 41 ]. Il27 , correlated with an immune–inflammatory imbalance in the pre-term [ 42 ], showed increased expression in Hmox1 −/− uteruses. Similarly, the upregulation of Il11 , was previously associated with inflammation and pre-eclampsia features in mice [ 43 ] and Il1b , linked to idiopathic recurrent implantation failure [ 44 ], indicated a pro-inflammatory milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Ran and his colleagues have reported a strong association between the preterm birth and the high levels of IL-27 in peripheral blood as well as the chorion of pregnant women which reflects systemic changes in both mother and fetus [32]. On the other hand, in healthy neonates, He and his colleagues have reported lack of any significant elevation of IL-27 in absence of infection through measuring its level in umbilical cord blood obtained from 33 healthy neonates without any risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data showed that IL-27 could release various inflammatory mediators such as IL-6, IFN-g, TNF-a, IL-1b, MCP-1, MMP9 and CXCL10 mainly via the ERK and JNK signaling pathways (24,25). Therefore, we investigated the inflammatory imbalance mediated by IL-27 in WISH and HMSMC cells.…”
Section: Il-27 Mediated Inflammation Imbalance Via the Erk Signaling Pathwaymentioning
confidence: 96%